A Secured IoT Based Advanced Health Care System for Medical Field using Sensor Network - Nalajala, Paparao; Bhagya Lakshmi, S (International Journal of Engineering and Technology, 2018)
In day to day life health awareness and controlling system is important to monitor those patientâ€™s physiological parameters frequently. In the recent health awareness environment those usage of IOT innovation organization acquires accommodation of professionals and also patients, since they are connected to different medical fields. A sensor node needs to be arranged on the apparent of the patient body will gather the entire signal from those wireless sensor and also send them of the body sensor node. Those connected sensor nodes on the patientâ€™s body can make in the structure of a wireless body sensor network furthermore they have the capacity with sense those heart beat rate, temperature of surroundings. That basic focus to this system may be on transmitting the individualsâ€™ patientâ€™s health watching parameters through wireless communication in crucial conditions. We propose a secure IOT built health awareness monitoring and will check that saline level of the patient.Â Â